Implementation of the Think Talk Write (TTW) Learning Model Assisted by Kahoot Game to Improve Indonesian Language Learning Outcomes of Fourth-Grade Elementary School Students - Arviani, Venni; Aria, Rizki (Journal Informatic, Education and Management (JIEM), 2025)
Indonesian language literacy skills in elementary schools still face challenges, especially in writing skills, and relatively low student learning engagement. This study aims to analyze the effectiveness of the Think Talk Write (TTW) learning model assisted by Kahoot in improving Indonesian language learning outcomes of fourth-grade elementary school students with a focus on descriptive text writing skills. The study used a classroom action research approach implemented in two cycles with the stages of planning, implementation, observation, and reflection. The subjects of the study were 20 fourth-grade students selected purposively. Data were collected through observation, essay tests, and questionnaires, then analyzed descriptively. The results showed that in the pre-cycle, student engagement only reached 25% with an average score of 57.95 and learning completeness of 30%. After the implementation of TTW assisted by Kahoot in the first cycle, student engagement increased to 60% with an average score of 70.5 and completeness of 65%. In the second cycle, student engagement reached 85% with an average score of 84.8 and learning completeness of 90%. These improvements reflect that the implementation of Kahoot-assisted TTW not only increased students' active participation in discussions and the use of interactive digital media but also significantly improved their writing skills. In conclusion, the Kahoot-assisted TTW model is effective in increasing student engagement and learning outcomes gradually throughout the learning cycle, as well as providing practical contributions to innovative and relevant learning strategies for 21st-century digital literacy needs.